Pemberdayaan Kelompok Pembudidaya Ikan Desa Totobo Melalui Pembuatan Pupuk Kompos dan Pakan Ikan Mandiri - Indrayani Indrayani; Rahim; Arman Pariakan; Qadri Fajri Adi; Willi Arfan (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
The potential of the vast ponds is not comparable to the production of the Totobo Mandiri Sejahtera group's partners. The priority problems are sub-optimal pond fertilization, inadequate provision of fish feed, and poor cultivation management. Through the Community Partnership Empowerment program, the implementing team conducted training on composting and making independent fish feed, and demonstrated tilapia and milkfish cultivation in ponds. The raw materials for compost include chicken manure, bran, lime, and EM4. The compost fermentation process lasts three weeks. The compost produced in this activity is 2,100 kg. The production of independent fish feed uses raw materials such as corn, bran, dried fish, and EM 4. Corn flour is used at 36%, fine bran at 36%, fish flour at 28%, and EM 4 at 1% or more. The farmer group partners produce 600 kg of fish feed. This PKM activity also created a demonstration plot for tilapia and milkfish cultivation, 10,000 tilapia and 5,000 milkfish. Tilapia is harvested after 3-4 months, and milkfish after 4-5 months. The target production of tilapia and milk fish is 500-800 kg/ha